Age-Stage, Two-Sex Life Table of Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) Experiencing Cadmium Stress - Bingyu He; Jiebo Zhang; Yang Hu; Yi Zhang; Jianan Wang; Chao Li (Insects)
Cadmium in agricultural soils has emerged as a substantial threat to crop health and yields through its bioaccumulation along the food chain, with further repercussions for the growth, development, and population dynamics of herbivorous insects. In this study, potted potato plants were treated with Cd2+ solutions at concentrations of 0 mg/kg, 30 mg/kg, 60 mg/kg, 90 mg/kg, and 120 mg/kg. Colorado potato beetles (Leptinotarsa decemlineata) were fed on potato leaves exposed to these varying concentrations of cadmium, and the effects on their growth and development were assessed. The results revealed that: 1. The developmental period, pupal stage, and pre-oviposition period of the first-instar larvae of L. decemlineata feeding on cadmium-contaminated leaves was significantly prolonged, while both the lifespan and fecundity were reduced. 2. Key population parameters, including the innate rate of increase (r), finite rate of increase (λ), net reproductive rate (R0), and gross reproduction rate (GRR), were evidently lower in cadmium-exposed L. decemlineata, while the average generation time did not show a significant difference. 3. Cadmium exposure also resulted in a remarkable reduction in survival and reproductive rates at specific life stages, along with an increase in the incidence of deformations in newly emerged adults. These findings underscore the detrimental effects of cadmium on both crop health and pest populations. This study holds valuable implications for more effective implementation of pest control strategies in the future, offering robust scientific evidence to support the safeguarding of food security.